Arbitrariedades existentes en las contrataciones de ínfima cuantía - Salazar Terán, Mónica Marianela (2015)
The present research work related to the analysis of administrative law from the standpoint of legal interpretation, and the legislative logic. Procurement of goods, services and works within the concept or legal norm smallest amount, is an important issue not only fashionable Ecuadorian law, but to the rest of Latin America because the countries of this region keep a common history, and the same is true of their legal frameworks. Within the framework I mention various concepts like: Concept of Directors, Concept of Public Administration Concept Amount, concept smallest amount, concept RUC, concept RISE concept of administrative discretion, Concept of suppliers, concept ORs. The doctrinal framework contains the analysis of administrative act, control administrative discretion, Public Procurement in Ecuador before the creation of the organic law of the national public procurement system, regulated and discretionary powers of the administration, administrative contracts, Similarities between the regulated and discretionary administrative acts, evidence observed in the scope. In the legal framework we find Constitution of the Republic of Ecuador, the Organic Law of the National Public Procurement System, General Regulation of the Organic Law of the National Public Procurement System and Resolution No. 062 issued to the casuistry of the hiring of negligible amount. In this research the way auscultare offer their services or sell their products providers State. Salability or limitations that put them contracting entities or institutions and public companies. I will achieve this through analysis of comparative law and a possible amendment to the resolution on specifics about the hiring of very small amount, their different causes